Trans-catheter edge-to-edge mitral valve repair in patients with acute decompensated heart failure due to severe mitral regurgitation – a single centre experience. (3rd October 2022) - Makmal, N; Silbermintz, N; Faierstein, K; Raphael, R; Moeller, C; Canetti, M; Maor, E; Kuperstein, R; Hai, I; Butnaru, A; Oren, D; Guetta, V; et al.
Abstract: Introduction: Recent series have demonstrated the benefit of trans-catheter edge-to-edge mitral valve repair (TEER) in acutely ill hospitalised patients with severe mitral regurgitation (MR) and intractable heart failure despite intensive intravenous therapy. We describe our cumulative experience with such patients at the Sheba Medical Centre over a 10 year period. Purpose: The purpose of this study was to evaluate the safety and efficacy of TEER in hospitalized patients with acute decompensated heart failure and severe MR that was deemed to play a major role in the patients' deterioration. Methods: We included 30 hospitalised patients with intractable heart failure and MR ≥3+ (20 males; mean age 74.2±10.6 years; 10 had cardiogenic shock). MR was primary in 4, secondary in 24 and mixed in 2 patients. Acute results were assessed by echocardiography prior to discharge and safety was evaluated clinically, according to the occurrence of procedure-related adverse events. Mortality data were drawn from the national death registry. Results: TEER devices were successfully implanted in 28 patients. Early (POD 1) procedure-failure was noted in one patient due to recurrence of flail. There was no peri-procedural mortality. Two patients were hemodynamically unstable during the procedure. One patient had peri-procedural access site bleeding necessitating blood transfusion. Following intervention, 16 patients required ICU care (mean stay 4.8±2.5 days), shock was recorded in 7 patients, 16 required hemodynamic support, and 8 required invasive ventilation. At 30 days 7 patients had died and an additional 4 died 1 to 6 months following intervention. However, mortality in the remaining patients was low with only 3 additional deaths up to 4 years after the procedure (80% of patients alive at 6 months). MR reduction was achieved in 24 patients (to ≤mild in 10 and to moderate in 11). At 12 months follow up MR severity was mild in 3 (37.5%) and moderate in 5 (62.5%) patients. Only 1 patient reported HF rehospitalisation during the year following the procedure. Conclusion: TEER for hospitalised patients with severe MR and intractable heart failure is safe, associated with high early mortality, and good long-term outcome for patients alive 6 months after the procedure. More research is needed to better characterise patients likely to benefit from TEER in this clinical scenario. Funding Acknowledgement: Type of funding sources: None.